The association of serum copper and peripheral arterial occlusive disease in males: A case control study. - Farzad, Fatemeh (Ezzat). (University of Ottawa (Canada), 1994)
One hundred and two patients with cases of intermittent claudication (IC) from the vascular surgery clinics of the Ottawa General and Ottawa Civic Hospitals along with 99 control patients from different outpatient clinics of these Hospitals were recruited. For each subject information about the background, medical history, and lifestyle were collected by a face to face interview, using a questionnaire. A number of blood tests, and clinical examinations were also done to complete the information about the exposure, outcome, and the potential risk factors. Serum copper status was obtained through atomic absorption spectrophotometry and PAOD status was assessed by means of Doppler ultrasound. The variable smoking group was shown to be an effect modifier in this data and therefore, the odds ratios for different strata of smoking group were calculated. The association of serum copper and PAOD was statistically significant in ex-smokers with an odds ratio of 2.38 (95% CI: 1.10, 5.15) for a five unit increase of serum copper. In conclusion, smoking and systolic blood pressure were strongly associated with PAOD. The association of serum copper and PAOD, after adjusting for the variable smoking group, systolic blood pressure, and all other study confounders, was reduced to a non-significant level. However, after considering the variable smoking group as an effect modifier, a statistically significant association between serum copper and PAOD was demonstrated in ex-smokers. (Abstract shortened by UMI.)
Keywords: Health Sciences, Pathology.